The genome sequence of the Dingy Shears, Fissipunctia ypsillon (Denis & Schiffermüller, 1775) - Holland, PWH; Boyes, D (F1000 Research Ltd, 2023)
We present a genome assembly from an individual female Fissipunctia ypsillon (the Dingy Shears; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 715.1 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the W and Z sex chromosomes. The mitochondrial genome has also been assembled and is 15.46 kilobases in length.